P.140 Radiological characteristics of brain metastases in non-small cell lung cancer relative to EGFR mutation status. (November 2021) - Hashmi, O; Younus, H; Bolton, L
Abstract : Background: Approximately 20-40% of patients with non-small cell lung cancer (NSCLC) will develop brain metastases (BM). The aim of this study was to investigate if Epidermal Growth Factor Receptor (EGFR) status of NSCLC alters the radiological appearances of BM. Also to compare differences in imaging features of BM occurring from EGFR-mutated NSCLC during treatment with Tyrosine Kinase Inhibitors (TKI) versus prior to treatment. Methods: A retrospective study was performed over a 5 year period of all patients with histologically proven NSCLC with BM and known EGFR status. 72 patients met the inclusion criteria. Radiological features were reviewed as well as number, size and location of BM. Results: 18/72 patients had EGFR-mutated NSCLC and of these 9 presented with BM while on TKI treatment. Patients with EGFR-mutated NSCLC had statistically significant higher occurrence of multiple BM (p=0.029) and BM in a central location (p=0.027). BM that occurred during TKI treatment appeared smaller and with minimal surrounding oedema. Conclusions: Given the propensity for multiple BM in EGFR-mutated NSCLC, vigilant imaging follow up would need to be considered. BM presenting while on TKI were more subtle, especially on Computed Tomography (CT), therefore careful follow up with Magnetic Resonance Imaging (MRI) may be required.